2016
DOI: 10.1097/cmr.0000000000000252
|View full text |Cite
|
Sign up to set email alerts
|

Anti-PD1-induced collagenous colitis in a melanoma patient

Abstract: Targeted immunotherapy has markedly improved the survival of melanoma patients. We report the case of a melanoma patient who developed a collagenous colitis under an anti-PD1 regimen. A 68-year-old woman was treated for a stage IV melanoma. An anti-PD1, pembrolizumab, was introduced after the failure of a first-line therapy with an anti-CTLA4. At cycle 14, pembrolizumab was interrupted because of grade 3 diarrhea. Histologic analysis of colon mucosa showed a thickened apical subepithelial collagen layer with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(46 citation statements)
references
References 14 publications
(13 reference statements)
5
41
0
Order By: Relevance
“…Although the findings in the stomach and duodenum fall within a narrow histological spectrum, ICI‐associated colitis is linked to a broad range of morphological alterations . It is of note that one‐quarter of all patients presenting with diarrhoea lacked detectable colonic histological abnormalities, and the majority of these cases showed ICI‐associated histological changes in the upper GI biopsies, an observation that reinforces the need to evaluate gastric and duodenal biopsies.…”
Section: Discussionmentioning
confidence: 81%
“…Although the findings in the stomach and duodenum fall within a narrow histological spectrum, ICI‐associated colitis is linked to a broad range of morphological alterations . It is of note that one‐quarter of all patients presenting with diarrhoea lacked detectable colonic histological abnormalities, and the majority of these cases showed ICI‐associated histological changes in the upper GI biopsies, an observation that reinforces the need to evaluate gastric and duodenal biopsies.…”
Section: Discussionmentioning
confidence: 81%
“…The KEYNOTE-001 trial, assessing the efficacy and safety of pembrolizumab, reported an incidence of 20% of diarrhoea, however only 4 cases of proven colitis out of 411 patients on pembrolizumab in the trial [1]. To date, there is one other published case of colitis with pembrolizumab, however they describe a collagenous colitis, in contrast to this example of lymphocytic colitis [2].…”
Section: Resultsmentioning
confidence: 88%
“…Immunotherapy has different adverse effects from tyrosine kinase inhibitors and non-specific chemotherapy, however; the medical background of a patient is very important. In one of our patients ulcerative colitis was considered an issue for immunotherapy treatment, since we know that this form of therapy induces colitis [14]. There is no way to actually compare these two treatments since their mode of action is based on two different concepts.…”
Section: Discussionmentioning
confidence: 99%